An eval uati on of past cattle di ppi ng practices in the former Ve nda area of Limpopo Provi nce, South Africa: Implications for sustai nable development - Horn, A.C. (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2014.